2010
DOI: 10.1260/0263-6174.28.8-9.789
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Adsorption of 2,4-Dinitrophenol from Aqueous Solution onto Bovine Bone Char by Immersion Calorimetry

Abstract: ABSTRACT:The immersion enthalpies of bovine bone char in aqueous solutions of 2,4-dinitrophenol (DNP) of 10, 30, 50, 70 and 100 mg/ᐉ concentration were determined. The results showed that the amount of DNP adsorbed and the variation in the immersion enthalpy depended upon the concentration of the solution. For low concentrations, both an increase in the immersion enthalpy and in the amount of DNP adsorbed occurred, whereas at high concentrations there was a corresponding decrease in the immersion enthalpy and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Doostmohammadi et al [14] found that when charring bovine and pig bones under air atmosphere the values of BET speci c surface areas were 2.2 and 44 m 2 /g, respectively. Murillo et al [15] reported surface area values of chicken pyrolysis in nitrogen atmosphere about 130 m 2 /g . More recently sh bone has been used as adsorbent materials for remediation of wastewater [ 7,[16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Doostmohammadi et al [14] found that when charring bovine and pig bones under air atmosphere the values of BET speci c surface areas were 2.2 and 44 m 2 /g, respectively. Murillo et al [15] reported surface area values of chicken pyrolysis in nitrogen atmosphere about 130 m 2 /g . More recently sh bone has been used as adsorbent materials for remediation of wastewater [ 7,[16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%